Water quality of the Bacauan River and Diday Creek during the rainy period - Pineda, Shienna Mae Maghuyop
Water samples from Bacauan River (Sites A, B, and D) and Diday Creek (Site C) were subjected to physico-chemical analyses (temperature, turbidity, color, pH, acidity, alkalinity, hardness, nitrate, solids, total dissolved solids) and microbiological analyses (TPC and MPN for total and fecal coliforms).